Are we Really Improving the Quality of Life after Hemiarthroplasty of the Hip in the Elderly? An Observational Study - T. Adarsh; Mruthyunjaya; C. S. Likhit; Nawab Akthar Khan (Journal of Orthopedics, Traumatology and Rehabilitation)
Introduction: Hip fractures are the major cause of disability and functional impairment in the elderly. Studies have correlated the results from treating femoral neck fractures; however, little has been described the quality of life (QOL) after hemiarthroplasty in these patients. Objective: An assessment of physical, psychological, social relationships, and environmental domains of QOL after hemiarthroplasty in elderly patients and to analyze the postsurgical impact on the activity of daily living and functional outcome of the hip. Methods: Prospective observational study was conducted on 100 elderly patients who underwent hemiarthroplasty. The hip function was scored with the Harris Hip Score (HHS) and activities of daily living were rated by the Barthel Index. Health-related QOL was rated by the World Health Organization QOL: Brief version applied before and 6 months after surgery. Results: There was fair to good HHS and decreased dependency in the activities of daily living with preserved function by the end of 6 months. Postsurgery ambulation showed that 30% of them used a walker for ambulation due to fear of falls. QOL improved but did not return to presurgery levels. The psychological domain was the most affected, followed by the environmental and social domains. Conclusion: Results showed the need for improvisation of various aspects of postoperative care such as designated rehabilitation protocols, fall clinics, psychotherapy and relaxation, and geriatric care for associated comorbidities. Implementing such a comprehensive specialty care approach along with good surgery will improve the QOL to presurgical level.